The Importance of Metabolism for Immune Homeostasis in Allergic Diseases - Rodriguez-Coira, Juan; Villaseñor, Alma; Izquierdo, Elena; Huang, Mengting; Barker-Tejeda, Tomás Clive; Radzikowska, Urszula; Sokolowska, Milena; Barber, Domingo (Frontiers in Immunology, 2021)
There is an increasing evidence that the metabolic status of T cells and macrophages is associated with severe phenotypes of chronic inflammation, including allergic inflammation. Metabolic changes in immune cells have a crucial role in their inflammatory or regulatory responses. This notion is reinforced by metabolic diseases influencing global energy metabolism, such as diabetes or obesity, which are known risk factors of severity in inflammatory conditions, due to the metabolic-associated inflammation present in these patients. Since several metabolic pathways are closely tied to T cell and macrophage differentiation, a better understanding of metabolic alterations in immune disorders could help to restore and modulate immune cell functions. This link between energy metabolism and inflammation can be studied by means of animal, human or cellular models. Analytical approaches rank from classic immunological studies to integrated analysis of metabolomics, transcriptomics and proteomics. This review summarizes the main metabolic pathways of the cells involved in allergic reaction with a focus on T cells and macrophages, and describes different models and platforms of analysis used to study the immune system and its relationship with metabolism.